A study on the prevalence of risk factors and presence of diabetic foot ulcers in T2DM patients in K. R. Hospital, Mysuru - S., Chandrashekar; Muralidhar, Suraj (International Surgery Journal, 2017)
Background: India is one of the top ten diabetes mellitus (DM) countries. Thus, the aim of this study was to survey the prevalence of DFU risk factors and DFU prevalence among type 2 diabetes mellitus (T2DM) patients. Methods: An epidemiological study was conducted on an outpatient basis in K. R. hospital, Mysuru. All T2DM participants were ≥ 18 years were included. Demographic and foot care behavior were assessed using minimum data sheet (MDS). Meanwhile, presence of risk factors was evaluated for neuropathy and presence of angiopathy was evaluated with ankle brachial index (ABI) by using a hand-held doppler both dorsal and posterior tibial. Results: At the end of study, 249 T2DM participants were enrolled. The prevalence of DFU risk factors was 55.4% (95% CI: 53.7% - 57.0%), and prevalence of DFU was 12% (95% CI: 10.3% - 13.6%). Conclusions: Even though the prevalence of DFU is high, identification associated factors for presence of risk and DFU has not been integrated into national guideline. Thus, preventive strategies should be introduced at early stage to prevent presence of risk and DFU.